2019
DOI: 10.3390/nu11020445
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association between Food Literacy and Food Insecurity

Abstract: Poor food literacy behaviours may contribute to food insecurity in developed countries. The aim of this research was to describe the apparent prevalence of food insecurity in adults at enrolment in a food literacy program and to examine the relationship between food insecurity and a range of independent variables. Individuals attending the Food Sensations® for Adults program in Western Australia from May 2016 to April 2018 completed a pre-program questionnaire (n = 1433) indicating if they had run out of money… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
119
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 68 publications
6
119
4
1
Order By: Relevance
“…Findings of the present study are in consistent with the earlier studies, mainly performed in the adults' population. In a study by Begley et al among a sample of Australian adults, all domains of the Australian food literacy model including planning and management, shopping, preparation, and cooking were independently associated with food insecurity [13]. Also, in another study among college students, it was found that very low food secure students had significantly lower cooking self-efficacy and food preparation scores compared with food secure students [15].…”
Section: Discussionmentioning
confidence: 95%
“…Findings of the present study are in consistent with the earlier studies, mainly performed in the adults' population. In a study by Begley et al among a sample of Australian adults, all domains of the Australian food literacy model including planning and management, shopping, preparation, and cooking were independently associated with food insecurity [13]. Also, in another study among college students, it was found that very low food secure students had significantly lower cooking self-efficacy and food preparation scores compared with food secure students [15].…”
Section: Discussionmentioning
confidence: 95%
“…Food literacy interventions have been shown to provide individuals with these skills that contribute to health [10,11]. However, the role that food literacy interventions play in addressing food security remains unclear [8,11]. Poor food literacy may exacerbate food insecurity, or experiencing food insecurity may restrict an individual's ability to practice food literacy behaviours and achieve adequate diet quality [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role that food literacy interventions play in addressing food security remains unclear [8,11]. Poor food literacy may exacerbate food insecurity, or experiencing food insecurity may restrict an individual's ability to practice food literacy behaviours and achieve adequate diet quality [8]. Hence, food literacy interventions cannot address the upstream determinants of food insecurity, such as access and affordability [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Findings of the present study are in consistent with the earlier studies, mainly performed in the adults' population. In a study by Begley et al among a sample of Australian adults, all domains of the Australian food literacy model including planning and management, shopping, preparation, and cooking were independently associated with food insecurity (13). Also, in another study among college students, it was found that very low food secure students had signi cantly lower cooking self-e cacy and food preparation scores compared with food secure students (15).…”
Section: Discussionmentioning
confidence: 95%
“…Findings from some recent studies have shown that in comparison to the food-secure households, those with food insecurity had lower FNLIT mainly characterized by unfavorable food choices and purchasing decisions as well as poor food preparation skills (13)(14)(15)(16). However, this evidence was limited to the adult population living in high-income and developed countries; thus, it is unknown whether these ndings are generalizable to the children and adolescents particularly in the low-income and developing nations.…”
Section: Introductionmentioning
confidence: 99%